Acute Cholecystitis-like Presentation in an Adult Patient with Gallbladder Agenesis: Case Report and Literature Review - Nahla Elzubeir; Kevin Nguyen; Muhammad Nazim (Case Reports in Surgery)
Introduction. Gallbladder agenesis (GA) is a rare congenital malformation, and majority are asymptomatic; however, symptomatic patients present with a clinical picture similar to biliary colic. Work up usually shows contracted gallbladder (GB) on ultrasound (US), and HIDA scan shows nonvisualization. Magnetic resonance cholangiopancreatography (MRCP) can be helpful in the diagnosis; however, the diagnosis without the latter can only be established intraoperatively. Management should be conservative treatment with antispasmodic drugs. Case Report. A 35-year-old female presented to the emergency department with nausea, vomiting, and worsening right upper quadrant (RUQ) abdominal pain. Vitals and laboratory values were unremarkable except for mild leukocytosis, and RUQ US reported “contracted GB, cholelithiasis, 4.2 mm wall thickness, and no ductal dilation.” Surgical consultation was prompted by the diagnosis of acute cholecystitis. The patient was transferred to the operating room for laparoscopic cholecystectomy; however, no GB was found, which was confirmed by intraoperative indocyanine green cholangiography. The procedure was aborted. Postoperatively, CT scan showed absent GB. A HIDA scan showed nonvisualization of the GB after 4 hours. Gastroenterology consultation was suggested to assess for peptic ulcer disease, stricture, or other etiology for her presenting symptoms, and the upper endoscopy showed gastritis. Upper GI with small bowel follow-through study showed mild delayed gastric emptying and contrast in the colon in 45 minutes. Conclusion. When US imaging findings are equivocal for nonvisualization of GB in a patient with no known history of prior cholecystectomy, additional imaging is required considering the diagnosis of gallbladder agenesis. MRCP is the test of choice. Management is usually conservative with smooth muscle relaxants without the need for surgical operation.